Freedom and nature in Schelling's philosophy of Art - Shaw, Devin Zane (University of Ottawa (Canada), 2009)
The goal of this thesis is to establish the centrality of the philosophy of art in Schelling's thought from the System of Transcendental Idealism (1800), through the period known as his absolute idealism or identity-philosophy (1801-1806), to the address Uber das Verhaltnis der bildenden Kunste zu der Natur of 1807. One of the central problems of previous interpretations of Schelling's philosophy of art is the lack of clear and comprehensive criteria for establishing the similarities and differences among his various presentations. In order to establish a measure for evaluating the continuity of Schelling's philosophy of art, I focus on demonstrating the structural features that are consistent from 1880 to 1807: (1) What philosophy constructs in the ideal, art produces in the real. Thus artistic activity is the highest human vocation (Bestimmung ) because practical philosophy can only approximate its object, which is the moral law. (2) While both the natural organism and the artwork embody the same identity of real and ideal, of necessity and freedom, the work of art overcomes these oppositions through the identity of conscious and unconscious production, whereas the organism's activity is unconscious. (3) Artistic production has a socio-political task: it aims to overcome the fragmentary condition of modernity through a new mythology and artistic renewal. All of these features are first outlined in the System of Transcendental Idealism and are maintained through 1807. I argue that they can be understood in relation to Schelling's ideas of freedom and nature. The philosophy of art emerges as a solution to the problem of how to show that human activity can be objectified within the real world. For the philosophy of art, the objective result is the artwork. Thus for Schelling, artistic production exhibits an ethic of free activity that was 'more free than freedom,' as freedom was conceived, in Kant and Fichte, as conformity to the moral law. Though he also thinks freedom as an infinite approximation to a regulative ideal, Schelling adds that artistic activity actually produces its own law, as beauty, in the harmony of form and content of the work, which exhibits the identity of freedom and necessity, and the self and nature. Art presents the absolute in the finite world, and makes possible a new mythology that can unify humanity. I conclude by arguing that Schelling abandons the philosophy of art when he shifts his concern to the relationship between freedom, revelation, and theology. Schelling's orientation turns from a hopeful future of humanity, realized in a new mythology, to a focus on Christian revelation, the figure of Christ and the idea of human freedom as positive capacity for good or evil. In this account, Schelling reduces the role of art to the production of a work of nostalgia for a lost connection to nature. Art is reduced to this role because Schelling now conceives of freedom, and virtue, as the highest activity of human being; but this idea of freedom is of an ecstatic or existential nature. Schelling elevates human freedom to the pinnacle of the system when he finally surpasses its conception as an activity that approximates the moral law. In the Philosophical Investigations into the Essence of Human Freedom of 1809, and the Stuttgart Seminars given a year later, freedom is rethought as a positive, ecstatic act of inner law-giving, which is realized as virtue.
Keywords: Philosophy.